Effect of mining speed on the activation characteristics of normal faults in deep thick coal seams - BIAN Hua; ZHAO Yixin; WANG Yuan; ZHAO Liangchen; YANG Zhe; HAO Jian (矿业科学学报, 2025)
This study attempts to investigate the effect of mining speed on the activation characteristics of normal faults. Taking the working face 8302 of the Xinjulong Coal Mine as the engineering background, this study explores the activation mechanism under the disturbance caused by hanging wall mining of normal faults. We investigated the effect of mining speed and the distance from the working face to the fault on the activation tendency of the fault through numerical simulation. Results show that the high-level stratum of normal fault is a high-risk area for fault plane activation, and its activation tendency index Ts is influenced by fault inclination θ and mining speed v of the working face. The fault activation in the mining process of the hanging wall working face can therefore be divided into 2 stages: quasi-static and activation. With the increase of v, the peak stress of surrounding rock decreases first and then increases. When v is 3 m/d, the peak stress reaches its minimum of 28.12 MPa. This could alleviate the stress concentration of surrounding rock. When the distance between the working face and the fault is less than 30 m, the risk of fault plane activation increases significantly. However, with a mining speed of 3 m/d, the activation tendency of fault plane reaches its minimum, and the distance causing fault activation is reduced to 40 m, outperforming those with other mining speeds.